Quality Time: What Baby Boomers Need for Parenting Their Generation Z Children: [Waktu Berkualitas: Hal yang Dibutuhkan Baby Boomers Dalam Pengasuhan Anak Generasi Z] - Aulia, Chika; Retnowati, Sofia; Reginasari, Annisa (ANIMA Indonesian Psychological Journal, 2023)
Changes in values, culture, and technology bring new demands on Generation Z parenting, especially by parents of the Baby Boomers generation. Although previous studies considered the generational gap between Baby Boomers parents and Generation Z as a myth, preliminary study raises an urgency to explore further the experiences of Baby Boomers parents in raising children from Generation Z. This study aims to explore the experiences of Baby Boomer parents in facing challenges and viewing opportunities in parenting Generation Z children. Utilizing a qualitative approach of Interpretative Phenomenological Analysis (IPA), this study involved three participants from the Baby Boomers generation who have children from Generation Z in Y city. The main data of this study were the transcripts of in-depth interviews, which lasted 90-120 minutes for each participant. The results of the analysis produced three themes, being: (1) the need to build parent-child closeness to bridge the generation gap; (2) parents' efforts to understand the world of children from Generation Z; and (3) parents' expectations for future of Generation Z adolescents. This study offered the implications for providing evidence from the latest study on parenting practices to uncover challenges and opportunities from the experience of Baby Boomers raising Generation Z. Perubahan nilai, budaya, dan teknologi membawa tuntutan baru dalam pola asuh Generasi Z, khususnya oleh orang tua dari generasi Baby Boomers. Meskipun studi sebelumnya menganggap kesenjangan generasi antara orang tua Baby Boomers dan generasi muda Generasi Z sebagai mitos, study pendahuluan memunculkan urgensi untuk menggali lebih jauh pengalaman orang tua Baby Boomers dalam mengasuh anak dari Generasi Z. Studi ini bertujuan untuk mengeksplorasi pengalaman orang tua Baby Boomers dalam menghadapi tantangan dan memandang peluang dalam mengasuh Generasi Z. Dengan menggunakan pendekatan kualitatif teknik Interpretative Phenomenological Analysis (IPA), studi ini melibatkan tiga partisipan dari generasi Baby Boomers yang memiliki anak dari Generasi Z di kota Y. Data utama studi ini adalah transkrip wawancara mendalam yang berlangsung selama 90-120 menit untuk tiap partisipan. Hasil analisis menghasilkan tiga tema, yaitu: (1) adanya kebutuhan membangun kedekatan orang tua-anak untuk menjembatani kesenjangan generasi; (2) upaya orang tua untuk memahami dunia anak dari Generasi Z; dan (3) harapan orang tua terhadap masa depan remaja Generasi Z. Studi ini menawarkan implikasi untuk menyediakan bukti dari studi terkini tentang praktik pengasuhan untuk mengungkap tantangan dan peluang pengalaman Baby Boomers mengasuh Generasi Z.